Evaluation of childhood absence seizures awareness and knowledge among parents in Saudi Arabia: A cross-sectional study - Hassan Ali Alradhi; Hassan Alturaiki; Jannat Bosbait; Nouf Alalmaei; Rahmah Alsawad; Taif Al Maqboul; Saleha Ahmed Khan; Nora AlMuslim (Journal of Family Medicine and Primary Care, 2025)
Introduction: Childhood absence seizures (CAS) are a form of epilepsy characterized by brief episodes of unconsciousness and staring spells. Despite their prevalence and potential impact on a child’s development, awareness and knowledge about CAS among parents in Saudi Arabia remain poorly understood. This study aimed to assess parents’ awareness and understanding of CAS in Saudi Arabia. Method: A cross-sectional survey was conducted among parents of children recruited from various regions in Saudi Arabia. The survey included questions related to demographic information, awareness of CAS, recognition of seizure symptoms, knowledge of appropriate actions during a seizure, and sources of information about seizures. Result: Our results indicate a lack of awareness and understanding of CAS among parents in Saudi Arabia. A significant proportion of respondents were unable to recognize common symptoms of absence seizures, often mistaking them for behavioral issues or other medical conditions. Furthermore, many parents demonstrated uncertainty regarding appropriate first-aid measures and misconceptions about the management of seizures. Conclusion: These findings underscore the need for targeted educational interventions aimed at improving parental awareness and knowledge of childhood absence seizures in Saudi Arabia. Healthcare providers play a crucial role in disseminating accurate information and addressing misconceptions about epilepsy.